Essential Oils: A Novel Approach for Anti-Microbial Therapy - Wani, Ashwini; Mange, Hiren; Vasudevan, Aishwarya (Natural Products Journal, The, 2022)
Overexploitation of antibiotics has led to significant challenges with antimicrobial resistance. The gravity of this trend has resulted in the rapid emergence of multi-resistant pathogens. Increased frequency to treat infections and the unfeasibility to reverse this resistance have burdened researchers in developing novel mechanisms to counteract and obstruct antimicrobial resistance. An effective medical strategy to control resistance was to develop new and potent antibiotics although, a sobering reality is that the product pipeline towards new antibiotics is inadequate. To ensure continued effective treatment of bacterial infections, there is an urgent need to control as well as conserve existing antibiotics through novel approaches. Utilization of Essential Oils (EO) in a multi-target anti-infective therapy addresses this need by targeting the mechanism of bacterial resistance and discovering synergism between EO’s antimicrobial properties to anti-infectives. When introduced into a pharmaceutical formulation, this novel and rational approach will open the door towards the development of a new generation of antimicrobials. Today, several essential oils have the ability to act as resistant modifying agents and enhance the antimicrobial activity of anti-infectives. This review article intends to focus on the effectiveness of essential oils on drug-resistant pathogens, mechanisms to counteract antimicrobial resistance, approaches to enhance efficacy, and explore potential applications.
Keywords: synergistic interaction